Reviewer Acknowledgement, 2020 - Jitti Hanprasertpong (Journal of Health Science and Medical Research, 2020)
The editor-in-chief of Journal of Health Sciences and Medical Research (JHSMR) would like to thank all our reviewers who have contributed to the journal during the period from October 1, 2019, through August 19, 2020.